2022
DOI: 10.1111/dmcn.15199
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation after paediatric acquired brain injury: Longitudinal change in content and effect on recovery

Abstract: Aim To describe cross‐sectional and longitudinal variation in neurorehabilitation content provided to young people after severe paediatric acquired brain injury (pABI) and to relate this to observed functional recovery. Method This was an observational study in a cohort of admissions to a residential neurorehabilitation centre. Recovery was described using the Pediatric Evaluation of Disability – Computer Adaptive Testing instrument. Rehabilitation content was measured using the recently described Paediatric R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Some studies show that BDNF is more neurotrophic in the brain, providing significant protection to both central and peripheral nerve cells, promoting effective repair in case of damage and normal functioning ( Lindholm & Saarma, 2022 ). MBP, a specific protein of oligodendrocytes and other neural tissues found in the vertebrate central nervous system, is released in large quantities into cerebrospinal fluid and then, into the blood after nerve tissue cells and myelin sheath are damaged or involved due to traumatic brain injury, often leading to an increase in the serum MBP level ( Forsyth et al, 2022 ). Studies reveal that serum MBP concentration is linked to the severity of the myelin injury of the white matter oligodendrocyte and destruction of the blood-brain barrier ( DiTommaso et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that BDNF is more neurotrophic in the brain, providing significant protection to both central and peripheral nerve cells, promoting effective repair in case of damage and normal functioning ( Lindholm & Saarma, 2022 ). MBP, a specific protein of oligodendrocytes and other neural tissues found in the vertebrate central nervous system, is released in large quantities into cerebrospinal fluid and then, into the blood after nerve tissue cells and myelin sheath are damaged or involved due to traumatic brain injury, often leading to an increase in the serum MBP level ( Forsyth et al, 2022 ). Studies reveal that serum MBP concentration is linked to the severity of the myelin injury of the white matter oligodendrocyte and destruction of the blood-brain barrier ( DiTommaso et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors' results quantified a known clinical phenomenon: for lower functioning children (or earlier in recovery) the focus of treatment is on the parents' emotions and skills, and the child's body function. 4 The focus in higher functioning children will be on training of adaptive skills in the child. This introduces a conundrum: how much was the changing therapy focus responsible for the observed recovery and how much did the child's recovery drive the change in therapy focus?…”
Section: Capturing the Active Ingredients Of Paediatric Neurorehabili...mentioning
confidence: 99%
“…3 In this respect, Jacoby et al have identified relevant predictors of QoL-related personal outcomes in children with IDD, such as sleep and community participation. 4 When variables such as these are included in logic models, the effect of interventions and policies can be better understood and, thereby, improved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Neuroplasticity is the ability of the brain to adapt and reorganize neural networks in response to environmental stimuli, experiences, and challenges; 17 work is ongoing to understand more about the doseresponse relationships within rehabilitation. 18,19…”
mentioning
confidence: 99%